A Local Fractional Variational Iteration Method for Laplace Equation within Local Fractional Operators - Yong-Ju Yang; Dumitru Baleanu; Xiao-Jun Yang (Abstract and Applied Analysis)
The local fractional variational iteration method for local fractional Laplace equation is investigated in this paper. The operators are described in the sense of local fractional operators. The obtained results reveal that the method is very effective.